THE IMPORTANCE OF USING MODERN PEDAGOGICAL TECHNOLOGIES IN PHYSICAL EDUCATION LESSONS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
The article discusses the importance of the use of modern pedagogical technologies in physical education and sports lessons, some recommendations on the formation of worldview and thinking, the formation of physical, spiritual and moral qualities.